Controlling Anxiety Mediates the Influence of Childhood Adversities on Risky Sexual Behaviors Among Emerging Adults. Issue 8 (13th October 2017) - Wong, Janet Yuen-Ha; Choi, Edmond Pui-Hang; Chan, Claudia Kor-Yee; Fong, Daniel Yee-Tak
Abstract : Relatively little research has assessed the exposure-response relationship of childhood adversities on engaging in risky sexual behaviors. Also, no previous research has examined the interrelationship among childhood adversities, adult anxiety and depressive symptoms, and risky sexual behaviors. This study aimed to investigate their interrelationships. We used data from a multisite survey of emerging adults aged 18 to 29 studying at four universities in Hong Kong between September and December 2015. Structural equation modeling (SEM) was used to examine the pathways from childhood adversities to risky sexual behaviors. Participants who had higher childhood adversity scores reported more severe adult anxiety symptoms (β = 0.20, p  = 0.002); and adult anxiety symptoms were associated with significantly more risky sexual behaviors (β = 0.46, p  < 0.0001). The model with adult anxiety symptoms as the mediator between childhood adversities and risky sexual behaviors showed good fit (root mean square error of approximation [RMSEA] = 0.04, comparative fit index [CFI] = 0.96, Tucker-Lewis index [TLI] = 0.94 and standardized root mean square residual [SRMSR] = 0.04). However, adult depressive symptoms failed to mediate between childhood adversities and risky sexual behaviors. This study demonstrates the link between childhood adversities and risky sexual behaviors via adult anxiety but not adult depressive symptoms. It is essential to reduce anxious symptoms in dealing with emerging adults who have risky sexual behaviors to prevent sexually transmitted infections (STIs) and unintended pregnancy.